Chinese nurses' self‐expression media image during COVID‐19 pandemic: A qualitative media image analysis - Huili Cao; Yangjie Chen; Xingyue He; Yejun Song; Qiaohong Wang; Hui Yang (Wiley, 2022)
Abstract Aim To explore and describe nurses' self‐expression media image during COVID‐19 pandemic in China. Background Nurses play an important role in COVID‐19 pandemic. Although nurses were widely reported by the media, which included praise for nurses and nursing work, the researches on how nurses expressed their self‐images were limited. Design Qualitative media analysis. Methods Qualitative media analysis was conducted from January to April 2020, the researchers collected images and texts of 16 Chinese nurses who take care of COVID‐19 patients. These images and texts were published on WeChat Moments by themselves. After analysed each image and text, researchers identified the denotative and connotative elements in each image and summarized each image in narrative way. Findings This study analysed 219 pictures and 15 short videos of 16 nurses' self‐expression in WeChat moments. In this study, the media image self‐expression of nurses were mostly positive. The images expressed by nurses in this study included care image; hero image; soldier image; female image; hope image and team image. Nurses rarely showed negative images in the media; The negative nurses image were expressed in hidden way, which included exhausted nurses image and fragile nurses image. Moreover, the nurse self‐expression media image emphasized the nursing professionalism, but less showed the nursing connotation. Conclusions The positive media image self‐expression of nurses should be encouraged. Nurse Managers should pay attention to the deficiency of nursing image expression and guide nurses to show the essence and connotation of nursing.